Modern Arabic short stories : a bilingual reader - Husni, Ronak; Newman, Daniel L. (Saqi, 2008)
This volume contains a collection of twelve stories by contemporary masters from Morocco to Iraq. In addition to works by writers already well-known in the West such as Idwar al-Kharrat, Fuad al-Takarli and Nobel Prize-winning Naguib Mahfouz, key authors whose fame has hitherto been restricted to the Middle East are also included. The collection features stories in both English and Arabic, prefaced by a brief author biography plus notes on context and background. Each story is followed by a glossary and discussion of problematic language points.